Environmental effects on automotive materials / Lindy Enggong - Enggong, Lindy (2002)
This text represents the contents of atmosphere and its effects to automotive materials. Atmospheric corrosion is one of the principal causes of economic losses in the automotive. The text is intended to provide the reader with an introduction to most of the topics that are of concern when a motorcar is being exposed to atmosphere and how vulnerable it is. It is hoped that this text will help to make us at least aware or possess knowledge of what are the general/common causes of automotive materials' failures together with its preventions as I believe that mostly the public society are dealing with cars in their daily routines. In other words, cars have become basic needs in this modem era for our mobility and strata. Readers' comments on the contents of this text will be welcomed so that their observations will be of great assistance for the further studies of effects of environment on automotive materials in the near future.